Metodologia para a implantação da viticultura de precisão na região de Santa Maria: fase de prospecção de campo - Silva, Juliano Reis da (2023)
The general objective of this work was to analyze and establish basis of a methodology to deploy precision viticulture in Santa Maria region. The specific objectives were: to correlate the spatial variability of the productivity to the spatial variability of the soil chemical parameters and vigor and NDVI parameters; diagnostic, identify and georeference the spatial variability of the productivity; and to assist the producer regarding the management of the field data through the use of precision agriculture tools. This research took place at Velho Amâncio Winery, in Itaara, the orchard had 1,23 ha (Latitude 29°39'10.16"S, Longitude 53°46'7.90"W). It was used a sampling grid of 50 points, where georefenced soil samples, vigor measurements and spectroradiometry measurements were taken. Spatial variability maps were made for all the researched parameters, and the vegetation indices were correlated through the Pearson correlation coefficient, at 5% level. The level of vigor, NDVI and productivity maps conformity was stablished by Kappa index. I was not possible to verify relation between the spatial variability of productivity and the spatial variability of soil chemical parameters. There was no relation between vigor, NDVI and productivity maps. It was possible to diagnose, identify and georeference the spatial variability of productivity. The results acquired by the PA tools and methodologies, were important to assist the producer in the activity management.